Strain rates in Greece using GPS measurements from 1994-2000 - Rontogianni, S.; Clarke, P.; King, M.; Lavallée, D.; England, P.; Parsons, B.; Floyd, M. (Bulletin of the Geological Society of Greece, 2007)
Fifteen Greek GPS campaigns from 1994-2001 are reprocessed in ITRF2000 using Bernese v4.2 software. The reference frame is navigated by 43 global, long running IGS sites, which are included in the coordinate final solution together with 280 local sites. A loosely constrained solution is derived. We combine the 221 daily SINEX files in a least squares approach with the TANYA software, producing the coordinate time series and the velocity field in a European Fixed reference frame. Sites around Chalkidiki and Grevena show a residual motion -10 mm/yr. Sites around Attica, Evvia, SE Peloponnisos, Aegean Islands have a SW residual motion reaching -40 mm/yr in South Peloponnisos. The Patras area shows a more southwesterly motion with respect to the rest of the sites, moving -30-35 mm/yr. Geodetic strain is derived by two methods: by discrete estimation within contiguous polygons, and by fitting a continuous minimum curvature surface to the velocity field.